2012
DOI: 10.5923/j.ijaf.20120201.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation with Sewage Effluent and Rhizobia Inoculation on Growth of Tropical Tree Legumes in Northeast Brazil

Abstract: The use of domestic sewage in the agriculture is an alternative for reduction of the pollution of rivers, preservation of resources hydrics and availability of water and nutritious for plants. An experiment was conducted to investigate the effects of irrigation with sewage effluent and rhizobia inoculation on growth parameters and macro and micronutrients contents in shoots of leguminous trees grown in an Alisol in northeastern Brazil. Irrigation with sewage effluent and rhizobium inoculation affected signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In both Acacia species, the MWR and PTWR water treatments affected on nodulation, they significantly increasing the number and dry weight of nodules. Similar results have been reported in other studies (Stamford and Silva 2000;Al-Fredan, 2006;Carvalho et al, 2012). Abd-Alla et al (2012, 1999 indicated that moderate application rates of sewage sludge increased the nodulation and nitrogen fixation in some legume crops.…”
Section: Results and Discussion 1 Growth And Nodulation Of Acacia Spsupporting
confidence: 80%
See 1 more Smart Citation
“…In both Acacia species, the MWR and PTWR water treatments affected on nodulation, they significantly increasing the number and dry weight of nodules. Similar results have been reported in other studies (Stamford and Silva 2000;Al-Fredan, 2006;Carvalho et al, 2012). Abd-Alla et al (2012, 1999 indicated that moderate application rates of sewage sludge increased the nodulation and nitrogen fixation in some legume crops.…”
Section: Results and Discussion 1 Growth And Nodulation Of Acacia Spsupporting
confidence: 80%
“…Several studies have also showed increasing in the growth parameters of trees and crops after irrigation with treated wastewater (Kiziloglu et al, 2008;Bedbabis et al, 2010;Akponikpèa, 2011;Pandey andSrivastava, 2012, andSelahvarzi andHosseini, 2012). Moreover, Carvalho et al (2012) found that the height and nodulation of Leucaena leucocephala and Mimosa caesalpiniaefolia significantly increased when treated with sewage effluent and inoculated with Rhizobium.…”
Section: Results and Discussion 1 Growth And Nodulation Of Acacia Spmentioning
confidence: 99%
“…Improved performance of crop (yield and yield attributes) in sewageirrigated fields was due to increased chlorophyll content and photosynthesis rate compared to bore well-irrigated crop (Table 4). De Carvalho et al (2012) also recorded improved legume performance with sewage irrigation. Among the sources of irrigation, sewage irrigation and alternate irrigation have added to nitrogen contribution and thus increased the N content and thus increasing protein and grain yield.…”
Section: Influence Of Land Types On Crop Growth Yield and Grain Qualitymentioning
confidence: 87%
“…This latter helps replenish N in the soil through N-rich litter-fall, along with root and nodule turnover which are necessary for plant growth and protection (Scheublin and Vander, 2006). Studies demonstrated the beneficial effects of inoculating legumes with rhizobia (de Carvalho et al, 2012;Ravikumar, 2012). Ceccon et al (2011) found that the inoculation with Sinorhizobium americanum could improve the Acacia farnesiana growth and the re-establishment of important plantsoil interactions in degraded areas.…”
Section: Introductionmentioning
confidence: 99%